QUANTIFICATION USING ULTRAVIOLET SPECTROSCOPY METHOD AND IN VITRO STABILITY STUDY OF NANOVESICULAR SYSTEM CONTAINING PHYTIC ACID - Arya, Malti; Gupta, Krishna P; Saraf, Shubhini A (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The quantification of drug and stability of nanoparticulate delivery systems is one of the major apprehensions in biomedical applications. The present research work was attempted to quantify phytic acid by utilizing ultraviolet (UV) spectroscopy method and to evaluate the stability of nanovesicular (niosomes) system containing phytic acid. Methods: Niosomes containing phytic acid were developed by thin-film hydration method. Nanoformulation was subjected to stability testing as per the International Council for Harmonisation (ICH) guidelines. The formulation was stored at 30°C±2°C and 65%±5% RH, samples were withdrawn at 15th, 30th, 60th, 90th, 120th, and 180th day of analysis and examined for the integrity of vesicular/particle size, polydispersity index, zeta potential, and percent encapsulation efficiency. Results: Prepared nanoformulation displayed a straight line (y=mx+c) equation of y=−0.0309x+1.0413. Optimized batch of niosomes, which was prepared including dicetylphosphate showed zeta potential value of −36±0.36. Stability study showed that prepared niosomal formulation was stable up to 180 days at room temperature. Conclusion: Findings of the current research work suggested that UV spectroscopy method can be effectively used for the quantification of phytic acid and niosomal formulation of phytic acid. The formulation was found to be stable as per the ICH guidelines for stability testing.